Advocacy to support climate and health policies: recommended actions for the Society of Behavioral Medicine. Issue 4 (25th May 2022) - Mendoza-Vasconez, Andrea S; McLaughlin, Elizabeth; Sallis, James F; Maibach, Edward; Epel, Elissa; Bennett, Gary; Nogueira, Leticia; Thayer, Julian; Dietz, William H
Abstract: Climate change poses serious threats to public health and is exacerbating health inequities. Policy changes are essential to mitigate climate change impacts on human and planetary health. The purpose was to describe recommendations by the Policy and Advocacy Subgroup of the Society of Behavioral Medicine (SBM) Climate Change, Behavior Change and Health Presidential Working Group (PWG). The Policy and Advocacy subgroup was comprised of experts in public health, climate policy, and health behavior change, who worked together to identify priorities and develop recommendations. We worked under the premise that building political will for climate policy action is the most urgent goal, and we recommended promotion of citizen advocacy for this purpose. Because citizen advocacy is a set of behaviors, SBM members can use behavioral science to identify and scale up interventions, working collaboratively with communities targeted for marginalization. Recommendations for SBM included establishing an organizational home for climate and health work, providing training and resources, engaging in climate advocacy as an organization, and networking with other organizations. Recommendations for a proposed SBM Climate and Health Committee, Council, or Special Interest Group included developing trainings and resources, seeking opportunities for networking and collaborations, and identifying a research agenda. Individual behavior changes are insufficient to address climate change; policy actions are needed. SBM and similar organizations can support their members to work in developing, evaluating, and scaling up advocacy interventions for action on climate policy to magnify the power of the health and medical sectors to protect planetary and human health. Lay Summary: Increasing advocacy for climate protection policies is a top priority. Recommendations are made for research and advocacy engagement by the Society of Behavioral Medicine and its members. Abstract : Increasing advocacy for climate protection policies is a top priority. Recommendations are made for research and advocacy engagement by Society of Behavioral Medicine and its members.